2014
DOI: 10.1292/jvms.14-0137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin A Status on Expression of Ucp1 and Brown/Beige Adipocyte-Related Genes in White Adipose Tissues of Beef Cattle

Abstract: We previously reported the presence of brown/beige adipocytes in the white fat depots of mature cattle. The present study examined the effects of dietary vitamin A on the expression of brown/beige adipocyte-related genes in the white fat depots of fattening cattle. No significant differences were observed in the expression of Ucp1 between vitamin A-deficient cattle and control cattle. However, the expression of the other brown/beige adipocyte-related genes was slightly higher in the mesenteric fat depots of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…The present results suggest that the modulation of expression levels of brown/beige adipocyte-related genes in the fat depots of cattle shown in previous studies (Asano et al, 2013;Kanamori et al, 2014) was achieved by altering the activity of the BMP pathway. In humans, the expression levels of components in the BMP pathway in adipose tissue appear to be related to adiposity.…”
Section: Genesupporting
confidence: 68%
See 4 more Smart Citations
“…The present results suggest that the modulation of expression levels of brown/beige adipocyte-related genes in the fat depots of cattle shown in previous studies (Asano et al, 2013;Kanamori et al, 2014) was achieved by altering the activity of the BMP pathway. In humans, the expression levels of components in the BMP pathway in adipose tissue appear to be related to adiposity.…”
Section: Genesupporting
confidence: 68%
“…We previously reported that the expression of Ucp1 in the subcutaneous fat depot was higher in cattle fed a concentrate diet than in those fed a roughage diet (Asano et al, 2013). Furthermore, the expression levels of brown/beige adipocyte-related genes (Seale et al, 2007) in the mesenteric fat depot were generally higher in cattle fed the vitamin A-deficient diet than in those fed the control diet (Kanamori et al, 2014). These findings prompted us to hypothesize that the expression levels of components in the BMP pathway are changed in the fat depots of cattle fed diets with a different ratio of roughage to concentrate or vitamin A-deficient diet.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations